Improving clinical examination in acute tibial fractures by enhancing visual cues: the case for always 'cutting back' a tibial back-slab and marking the dorsalis pedis pulse. (August 2016) - Thomas, Alasdair; Kimber, Cheryl; Bramwell, Donald; Jaarsma, Ruurd
Abstract: Look, feel, move is a simple and widely taught sequence to be followed when undertaking a clinical examination in orthopaedics (Maher et al., 1994;McRae, 1999 ; Solomon et al., 2010). The splinting of an acute tibial fracture with a posterior back-slab is also common practice; with the most commonly taught design involving covering the dorsum of the foot with bandaging (Charnley, 1950; Maher et al., 1994; McRae, 1989). We investigated the effect of the visual cues provided by exposing the dorsum of the foot and marking the dorsalis pedis pulse. We used a clinical simulation in which we compared the quality of the recorded clinical examination undertaken by 30 nurses. The nurses were randomly assigned to assess a patient with either a traditional back-slab or one in which the dorsal bandaging had been cut back and the dorsalis pedis pulse marked. We found that the quality of the recorded clinical examination was significantly better in the cut-back group. Previous studies have shown that the cut-back would not alter the effectiveness of the back-slab as a splint (Zagorski et al., 1993). We conclude that all tibial back-slabs should have the bandaging on the dorsum of the foot cut back and the location of the dorsalis pedis pulse marked. This simple adaptation will improve the subsequent clinical examinations undertaken and recorded without reducing the back-slab's effectiveness as a splint.